IMPLEMENTASI STRATEGI CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN DAMPAK TERHADAP KEHIDUPAN MASYARAKAT - Silalahi, Zefanya Louis Edo; Pradana, Bayu Ilham (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Corporate Social Responsibility is a form of accountability performed by companies. Along with the advancement of civilization, in order to bring good corporate governance, good corporate citizen, and good business ethic, companies are more encouraged to engage in sustainable development. The objective of this study is to identify the implementation and the impact of CSR conducted by PT. Pupuk Kaltim. The data was harvested through interviews, observations, and library researches. The analyses were performed using data collection, data reduction, data display, and conclusion. This study finds that CSR implementation by PT. Pupuk Kaltim has run well. The impact is improvement in public welfare. Partnership programs, territorial improvement, and environmental protection are the manifestation of sustainable development run by the company.